Ayurveda Management of Emphysema of the Lungs - Acharya, Shripathi; Acharya, Rajeshwari (International Research Journal of Ayurveda & Yoga, 2020)
Chronic lung disorders are occurring commonly in Indian population. Altered food habits, faulty life style, smoking, air pollution has resulted in increase in pulmonary disorders. Among these, Chronic Bronchial Asthma, COPD, Bronchiectasis and Emphysema of the lung have been increased. Any patient of Bronchial Asthma who are not treated properly or in chronic course lead to emphysema in the end. Patients of emphysema will have barrel shaped or pigeon shaped chest and increased resonant note on percussion. These patients will have thick and productive sputum on expectoration. In Ayurveda respiratory diseases occur due to involvement of Pranavaha Srotas where cough, breathing difficulties, disturbed respiratory pattern occurs . Ayurveda medicines has positive role in the management of Emphysema of the lung. Formulations like Poornachandrodaya rasa, Hiranyagarbha pottali, Malla sindoora, Tala sindhoora, Rasamanikya, Siddha makaradwaja, Kanakasava, Somasava, Vasakarista, Taleesadi choorna and Sitopaladi choorna are commonly used in the management of Emphysema. These formulations are having the ingredients with actions like immunomodulatory, anti infective, anti-bacterial, krimighna, bronchodilator, expectorant, rasayana, ojaskara, vayasthapana and mucolytic action.The present paper highlights about the role of Ayurveda medicines in the management of Emphysema of the lungs.